The development of export trade of European industrial products and its financing - SARACENO, P. (PSL Quarterly Review, 2014)
A plan for medium-term financing of international trade that does not require the use of dollars has recently been developed by a group of European bankers in consultation with experts of the United Nations Economic Commission for Europe. The principal author presents the plan here, except for slight retouches, in its original form of a study prepared in 1948 in connection with discussions which took place in the Permanent Economic Committee of the World Federation of United Nations Associations (WFUNA). JEL: F10, F15, L52